2012
DOI: 10.1590/s1677-55382012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation ratio efficacy might be a better predictor to assess learning curve of holmium laser enucleation of the prostate

Abstract: ARTIcLe InfO _______________________________________________________________ _____________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
5
31
2
Order By: Relevance
“…The enucleated tissue weight in this study tended to be less than that of transition zone volume on TRUS, likely owing to the vaporization caused by the laser. These findings were similar to those from other studies [1] and our previous study [17]. Hence, we believe that complete removal of adenoma tissue in extremely large prostates is feasible.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The enucleated tissue weight in this study tended to be less than that of transition zone volume on TRUS, likely owing to the vaporization caused by the laser. These findings were similar to those from other studies [1] and our previous study [17]. Hence, we believe that complete removal of adenoma tissue in extremely large prostates is feasible.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the short-term results of previous studies of HoLEP in smallor moderate-sized prostates, which reported significant improvements of IPSS and uroflowmetric parameters [8,17,18]. The discordance of PVR is likely owing to the small sample size (n=6) in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Morcellation efficiency was defined as enucleated prostate weight divided by morcellation time [14]. Continuous variables were analyzed using the t-test and the Mann-Whitney test, and nominal and categorical variables using the Chi-square test and Fisher's exact test.…”
Section: Methodsmentioning
confidence: 99%
“…The surgical procedure for HoLEP at our institution has been previously described in detail [10,11,12,13,14]. Patients were instructed to discontinue anticoagulant medication at least 5 days before surgery.…”
Section: Methodsmentioning
confidence: 99%